KONTRIBUSI MOTIVASI DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN TEKNIK ELEKTRONIKA DASAR SISWA KELAS X JURUSAN TEKNIK AUDIO VIDEO DI SMKN 2 SOLOK - Deri Harsan Jhoni; Hanesman Hanesman; Almasri Almasri (Universitas Negeri Padang, 2017)
The purpose of this study is to reveal how much the presence Contributionsmotivation and learning environment on learning outcomes in basic electronicsengineering subjects in class X student engineering audio video Di SMKN 2 Solok.This research is a descriptive correlational. The type of data needed in the researchis the primary data and secondary data. The primary data is data obtained directly fromrespondents regarding Contributions motivation and learning environment, whilesecondary data is student learning outcomes obtained from subject teachers basicelectronics engineering. The population in this study is a Class XI student at SMKN 2Solok TAV as many as 56 students. While the sampling technique of this study is a random(Simple random sampling).Data were analyzed using Microsof Excel and SPSS (Statistical Product andService Solution) version 22.0. From the results, motivation and learning environmentjointly contribute significantly to student learning outcomes SMKN 2 Solok amounted to32.08%, (2) learning motivation contribution significantly to student learning outcomesSMKN 2 Solok amounted to 22.89%, (3) the learning environment contribute significant tostudent learning outcomes SMKN 2 Solok amounted to 23.40%. So it can be concluded thatthe Learning Motivation and Learning Environment Contribution To Student LearningOutcomes in SMKN 2 Solok, the better the motivation to learn and learning environment,the higher the learning outcomes.Keywords: Motivation, Learning Environment, Learning Outcomes.